High Fe and Ca contents contribute to geologically-high As but bioaccessibly-low As in karstic residential soils - Yuanchen Zhang; Guobing Lin; Chenjing Liu; Zhongfang Yang; Lena Q. Ma (Soil & Environmental Health)
Karstic soils are often naturally-high in As contents, primarily due to the secondary enrichment during soil weathering from carbonate rocks. However, the As risk via soil exposure for residents in karst areas remains unclear. In this study, we collected 32 residential soils from rural karst area in Guangxi and measured their total As, Fe, Ca and organic C contents. To assess their health risk, we determined and compared bioaccessible As, Fe, and Ca using three in vitro assays (solubility bioaccessibility research consortium-SBRC, physiologically based extraction test-PBET, and in vitro gastrointestinal methods-IVG). The karstic soils showed high As contents at 8.09–256 ​mg ​kg−1, averaging 58.2 ​mg ​kg−1, but low bioaccessible As at 0.386–0.977 ​mg ​kg−1, averaging 0.783 ​mg ​kg−1. The As bioaccessibility was low at 1.14–3.34%, averaging 1.97%, suggesting a low health risk to humans via incidental oral ingestion. The high Fe content averaging 74.8 ​g ​kg−1 may have contributed to As enrichment in karstic soils, with a positive correlation of R2 ​= ​0.623. Further, the low Fe bioaccessibility at 0.28% in the gastric phase of SBRC indicated that Fe was poorly soluble in simulated gastrointestinal solution, which may have contributed to low bioaccessible As (R2 ​= ​0.360). Besides, bioaccessible Ca and soil organic C may also play a role with R2 ​= ​0.404−0.449. This study sheds light on the high total As contents but low bioaccessible As in residential soils, indicating the low health risks via incidental oral ingestion in karst areas.